Evolvability and evolutionary rescue. Issue 4 (2nd February 2021) - Feiner, Nathalie; Brun‐Usan, Miguel; Uller, Tobias
Abstract: The survival prospects of threatened species or populations can sometimes be improved by adaptive change. Such evolutionary rescue is particularly relevant when the threat comes from changing environments, or when long‐term population persistence requires range expansion into new habitats. Conservation biologists are therefore often interested in whether or not populations or lineages show a disposition for adaptive evolution, that is, if they are evolvable. Here, we discuss four alternative perspectives that target different causes of evolvability and outline some of the key challenges those perspectives are designed to address. Standing genetic variation provides one familiar estimate of evolvability. Yet, the mere presence of genetic variation is often insufficient to predict if a population will adapt, or how it will adapt. The reason is that adaptive change not only depends on genetic variation, but also on the extent to which this genetic variation can be realized as adaptive phenotypic variation. This requires attention to developmental systems and how plasticity influences evolutionary potential. Finally, we discuss how a better understanding of the different factors that contribute to evolvability can be exploited in conservation practice. Graphical Abstract: Plasticity can play a role in adaptation to novel environments, for example when urban habitats are colonized. Depending on the plastic responses of the colonizing organisms, two alternative adaptive solutions ‐ becoming cryptic or becoming bold ‐ are possible. Research Highlight: Conservation concerns would benefit greatly if researchers could predict if and how populations will evolve. We outline the opportunities and challenges to make studies of evolvability matter to conservation practice.